Use of Ella® to facilitate drug quantification and antidrug antibody detection in preclinical studies. (8th January 2019) - Wessels, Uwe; Mackeben, Klaus; Stubenrauch, Kay
Aim: To explore the usability of the Ella ® platform for preclinical analysis of therapeutic antibodies and antidrug antibodies (ADA).Experimental: Two well-established ELISAs for the measurement of human IgG and ADA were transferred to the Ella platform. ELISA and the Ella platform were compared using assay qualification data and results of preclinical sample analysis.Results: The performance and results of both assays on the Ella platform were comparable to those of ELISA. The Ella platform had several advantages, including time efficiency, low sample consumption and a high degree of automation. ADA were assessed on Ella for the first time.Conclusion: The Ella platform is a promising tool for the analysis of preclinical samples.